Purification by silica gel chromatography using dialysis tubing and characterization of sophorolipids produced from Candida bombicola grown on glucose and arachidonic acid - Shah, Sachin; Prabhune, Asmita (Biotechnology Letters, 2007)
The yeast Candida bombicola (ATCC 22214) grown on primary carbon source glucose (100 g l(-1)) and secondary carbon, arachidonic acid (2 g l(-1)) produced mixture of sophorolipids up to 1.44 g l(-1). The crude product was a heterogeneous mixture of sophorolipids, which are glycolipids of sophorose linked to the fatty acid through glycosidic bond between omega and omega-1 carbon of arachidonic acid. The derived sophorolipids were isolated by silica gel chromatography using dialysis tubing. The purified sophorolipids were characterized by ESI-MS and FT-IR. Acid hydrolysis of the resolved sophorolipids were characterized by ESI-MS for the presence of 20-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (20-HETE) and 19-hydroxy-5Z,8Z,11Z,14Z-eico-satetraenoic acid (19-HETE), compounds of pronounced pharmaceutical importance.
Keywords: 19-HETE; 20-HETE; arachidonic acid; electrospray soft ionization mass spectroscopy; silica gel chromatography; Sophorolipid

COLL 41-studies in biosurfactants: sophorolipids - Momin, Shamim A.; Prabhune, Asmita; Sonchal, Bhushan P.; Shah, Sachin; Kothekar, Shrinivas C. (235th American-Chemical-Society National Meeting, 2008)
235th American-Chemical-Society National Meeting, New Orleans, LA, APR 06-10, 2008
Keywords: Biosurfactants; Candida bombicola ATCC 22214; Fermentation Process; sophorolipids